Pengaruh Current Ratio, Debt to Equity Ratio, Return on Assets dan Return on Equity terhadap Harga Saham pada Perusahaan Jasa Sub Sektor Telekomunikasi yang terdaftar di Bursa Efek Indonesia (BEI) Tahun 2018-2021 - Intan Novia Astuti; Ainul Ridha; Sisca Mediyanti (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2023)
This study aims to determine the effect current ratio, debt to equity ratio, return on assets and return on equity on stock prices in Telecommunications Sub Sector Service companies listed on the Indonesia Stock Exchange (IDX) for 2018-2021. The population in this study are 19 telecommunications sub-sector service companies listed on the Indonesia Stock Exchange (IDX) for 2018-2021. The sample collection method used purposive sampling method in order to obtain 16 companies that met the criteria as samples and obtained 64 observational data. The data analysis method used is multiple linear regression analysis. The results showed that simultaneously Current Ratio (CR), Debt To Equity Ratio (DER), Return On Assets (ROA), Return On Equity (ROE) affect stock prices. Partially, Current Ratio (CR) and Debt to Equity Ratio affect stock prices. Return On Assets (ROA) and Return On Equity (ROE) have no effect on stock prices.